Effect of chemical ions on oil palm midribs and leaves by direct electric voltage treatment - Defrianto Defrianto; Suhardi Suhardi; Dewi Indriyani Roslim; Awitdrus Awitdrus (Science, Technology, and Communication Journal, 2023)
The productivity of palm trees grown is generally measured in monthly and yearly periods, but on a shorter time scale, it is particularly measured by the plant maintenance of palm trees. Consideration of the general productivity in time is how to produce good fruit fertilizer (chemical aspect), healthy plants, fast growing and evolving (agricultural aspect), and genetic type of palm that grows (biological aspect). However, the growth and production on the physical aspect is still less attention. Through physical treatment, the growth of palm trees can be optimized to support aspects of the previous aspects, as it has been proven in advanced countries on the plant's aloe vera, avocado, and pine trees. In this paper, the methodology proposes a direct current voltage treatment to the palm tree that can accelerate the flow of ions to grow and develop nutrients. The palm tree samples are aged 1 to 5 years corresponding to the provision of 10, 16, 25, 35, and 50 V for each of the ages of the palm tree respectively. Identifying samples before and after treatment by electricity is based on the geometry of leaves, midribs, and ions effect. There have been reduced and increased levels of nutrients. This identification can optimize the productivity of palm trees.